Efficacy and safety of bimekizumab as add-on therapy for rheumatoid arthritis in patients with inadequate response to certolizumab pegol: a proof-of-concept study. Issue 8 (8th August 2019) - Glatt, Sophie; Taylor, Peter C; McInnes, Iain B; Schett, Georg; Landewé, Robert; Baeten, Dominique; Ionescu, Lucian; Strimenopoulou, Foteini; Watling, Mark I L; Shaw, Stevan
Abstract : Objective: Evaluate the efficacy and safety of dual neutralisation of interleukin (IL)-17A and IL-17F with bimekizumab, a monoclonal IgG1 antibody, in addition to certolizumab pegol (CZP) in patients with rheumatoid arthritis (RA) and inadequate response (IR) to certolizumab pegol. Methods: During this phase 2a, double-blind, proof-of-concept (PoC) study (NCT02430909 ), patients with moderate-to-severe RA received open-label CZP 400 mg at Weeks 0, 2 and 4, and 200 mg at Week 6. Patients with IR at Week 8 (Disease Activity Score 28-joint count C-reactive protein (DAS28(CRP))>3.2) were randomised 2:1 to CZP (200 mg every 2 weeks (Q2W)) plus bimekizumab (240 mg loading dose then 120 mg Q2W) or CZP plus placebo. The primary efficacy and safety variables were change in DAS28(CRP) between Weeks 8 and 20 and incidence of treatment-emergent adverse events (TEAEs). Results: Of 159 patients enrolled, 79 had IR at Week 8 and were randomised to CZP plus bimekizumab (n=52) or CZP plus placebo (n=27). At Week 20, there was a greater reduction in DAS28(CRP) in the CZP-IR plus bimekizumab group compared with the CZP-IR plus placebo group (99.4% posterior probability). The most frequent TEAEs were infections and infestations (CZP plus bimekizumab, 50.0% (26/52); CZP plus placebo, 22.2% (6/27)). Conclusions: PoC was confirmed based on the rapid decrease in disease activity achieved with 12 weeks of CZP plus bimekizumab. No unexpected or new safety signals were identified when neutralising IL-17A and IL-17F in patients with RA concomitantly treated with CZP, but the rate of TEAEs was higher with dual inhibition.